ANALISIS KADAR TIMBAL DARAH DAN PENYAKIT HIPERTENSI PADA PETUGAS STASIUN PENGISIAN BAHAN BAKAR UMUM DI KOTA MANADO - Kawatu, Paul (CHEMISTRY PROGRESS, 2009)
The contamination of gasoline is getting higher along with the increasing number of cars up to this days.With the improvement of lead polutant (Pb) on the air, human being will get more risk of being exposed bythe danger of this substance. Various effect of lead exposure toward human health are hypertension andoccupational fatigue. The workers of SPBU is a high risk group that was exposed by lead, since they wereused to exposed with fume or gasoline and smoke of cars. This research was aimed to find out therelationship between blood lead level and the incident of hypertension toward workers of SPBU in Manadomunicipality.This was a cross sectional research with 96 respondents. The bivariat analysis showed thatblood lead level had positive and significant correlation and yet weak toward hypertension incident(p<0,05; rpbis=0,324; rpbis2=0,105). The multivariate analysis showed that the blood lead level was asignificant predictor (p<0,05) toward hypertension incident with effective contribution of 6,74%. Theresearch result showed that the blood lead level had significant relationship and predictor towardhypertension after the other predictors being controlled. Therefore, prevention effort on the impact of leadthrough continuous health examination and application of health principles and occupational safety for theSPBU workers is necessaryÂ Keywords : blood lead level, hypertension